2011
DOI: 10.1002/jcp.22630
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage‐induced expression and release of matrix metalloproteinase 1 and 3 by human preadipocytes is mediated by IL‐1β via activation of MAPK signaling

Abstract: Obesity is associated with a chronic low-grade inflammation and increased macrophage infiltration in adipose tissue. Matrix metalloproteinases (MMPs) are involved in adipose tissue remodeling and inflammatory responses in obesity. This study investigated whether macrophage-derived factors modulate expression and secretion of MMP1 and MMP3 in human preadipocytes. The potential mediators and signaling pathways were also explored. MMP1 and MMP3 were primarily expressed and secreted by preadipocytes and dramatical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 52 publications
3
44
0
Order By: Relevance
“…These findings supported the concept that factors in addition to absolute weight burden, such as qualitative features of AT, might be important determinants of CVD [33]. Mechanistically, macrophage-induced expression and release of MMP-1 and MMP-3 by human preadipocytes is mediated by IL-1 β activation [34]. The macrophage-derived apoptosis inhibitor of macrophage (AIM) protein is increased in blood and is incorporated into adipocytes, thereby inducing lipolysis in AT.…”
Section: Obesity Is a Chronic Inflammatory Diseasesupporting
confidence: 66%
“…These findings supported the concept that factors in addition to absolute weight burden, such as qualitative features of AT, might be important determinants of CVD [33]. Mechanistically, macrophage-induced expression and release of MMP-1 and MMP-3 by human preadipocytes is mediated by IL-1 β activation [34]. The macrophage-derived apoptosis inhibitor of macrophage (AIM) protein is increased in blood and is incorporated into adipocytes, thereby inducing lipolysis in AT.…”
Section: Obesity Is a Chronic Inflammatory Diseasesupporting
confidence: 66%
“…However, we cannot rule out that MCF-7 cells in co-culture with fat tissue may induce an increase of MMP-1 expression in the fat tissue itself. Gao and Bing reported that MMP-1 is expressed and secreted by preadipocytes and to a much lesser extent in mature adipocytes, but can be stimulated by macrophage-conditioned medium in both cells types [49]. …”
Section: Discussionmentioning
confidence: 99%
“…At the level of the adipocyte, IL-1β has recently been shown to inhibit insulin signal transduction, this involving reduced expression of signalling proteins (Gao & Bing, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Human recombinant IL-1β (Sigma, UK) was added to the wells at a dose of 2 ng/ml which previous studies have demonstrated provides a maximal, or near-maximal, response in human fat cells (Gao & Bing, 2011). Groups of adipocytes were treated with IL-1β for either 4 h or 24 h (from previous pilot studies, a near maximal response was evident at 4 h); control cells were incubated without IL-1β.…”
Section: Cell Culturementioning
confidence: 99%